The Effect of Der on Stock Return in Manufacturing Companies of Consumption Industrial Goods Sector - Heru Prayitno, Yogo; Haizam Mohd Saudi, Mohd; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of DER on stock returns. This research is motivated by several manufacturing companies in the consumer goods industry sector showing fluctuating stock returns during the 2013–2017 period. A stock return is a profit in the form of a rate of return on a security owned by an investor. DER is a ratio that measures debt held by a company with shareholders' equity The population of this study is a consumer goods manufacturing sector listed on the Indonesia Stock Exchange in the period 2013-2017, which is 51 companies. The sampling technique used in this study was the purposive random sampling method. There were 27 samples of manufacturing companies in the consumer goods industry sector listed on the IDX that had met certain criteria that had been adjusted. The types of data in this study are quantitative data in the financial statements during the period 2013-2017 obtained from the Indonesia Stock Exchange and IDN Financials sites. The results showed that the DER did not affect stock returns.